BUZZER: POLITIC’S INTEREST AND MASLAHAH: - - Amanatus Sholihah (Politea : Jurnal Politik Islam, 2022)
Abstract Indonesia’s political tensions are heating up lately. It has been showed by some commotions happen after populism and political identity was buzzed since general election on 2019. These commotions were escalated when the political elites and parties involved political buzzer within democracy. Some sensitive issues spread by political buzzer through campaign narrations and it causes society segmented into two parts: “Cebong” and “Kampret”. They have been attacking each other both in social media and in real life; or both psychological and physical. It keeps happen now. This paper wants to learn why are buzzers appear together with political events include general election, and how is buzzers in Islamic perspective. This is descriptive paper with literature review’s method that conducting some doc5uments, journals, news relating with problem research. Then the result shows that buzzers appear in political events because it is one of political instruments who are needed in digital era massively. In Islamic perspective, buzzers gave maslahah (positive impact) to the democracy. But in another hand, their activities on social media such as produces a hoax, etc. categorized as fitnah, ghibah and namimah that is gave madharat too. Then the ways to handle some negative impacts of buzzers in social media are optimyze the roles and synergies of all parties from the government, political elites, parties, and educate society to minimize political buzzer in spreading hate speech, black campaign, and hoax. So as to create healthy political participation both in social media and in social life. Keywords: buzzer, political interest, and maslahah.